Keterampilan Menulis Pantun Berbahasa Banjar Sebagai Upaya Pelestarian Budaya Lokal - Khairiyah, Hana; Noortyani, Rusma (Universitas PGRI Semarang, 2025)
This study aims to examine the skills of seventh-grade students at MTs. Puteri Al-Amin Martapura in writing pantun (a traditional form of Indonesian poetry) in the Banjar language as an effort to preserve local culture. Using a qualitative descriptive method, data were collected from 66 pantun produced by students, which were analyzed based on internal structures, values, and language use. The findings indicate that students demonstrate a good understanding of the fundamental structure of pantun, adhering to the rhyme scheme a-b-a-b, although some face challenges in selecting appropriate diction and relevant themes. The pantun reflects cultural, moral, educational, and religious values, embodying local wisdom. External factors, such as family environment and personal experiences, significantly influence students' writing skills. Contextual and creative learning approaches yielded positive outcomes in enhancing linguistic competence and cultural understanding. This study concludes that integrating pantun writing into education enhances students' writing skills while fostering the preservation of Banjar culture in South Kalimantan.